Recommended practice for calibrating vacuum gauges of the ionization type - Fedchak, James A. (J Vac Sci Technol A, 2018)
This article represents a recommended practice for the calibration of ionization gauges using the comparison method. In this method, ionization gauges are compared to a working standard that has an SI traceable calibration. The ionization gauge is either of the hot-cathode ionization type or the cold-cathode ionization type. Details of the calibration apparatus, the principle of operation of the gauges, data analysis, uncertainty budget, and reporting the uncertainty are given.